Trigonometric delights - Maor, Eli (Princeton science library., 2020)
A fun, entertaining exploration of the ideas and people behind the growth of trigonometryTrigonometry has a reputation as a dry, difficult branch of mathematics, a glorified form of geometry complicated by tedious computation. In Trigonometric Delights, Eli Maor dispels this view. Rejecting the usual descriptions of sine, cosine, and their trigonometric relatives, he brings the subject to life in a compelling blend of history, biography, and mathematics. From the proto-trigonometry of the Egyptian pyramid builders and the first true trigonometry developed by Greek astronomers, to the epicycles and hypocycles of the toy Spirograph, Maor presents both a survey of the main elements of trigonometry and a unique account of its vital contribution to science and social growth. A tapestry of stories, curiosities, insights, and illustrations, Trigonometric Delights irrevocably changes how we see this essential mathematical discipline.